2018
DOI: 10.1111/jpn.12901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid bacteria and smectite after aflatoxin B1 challenge on the growth performance, nutrient digestibility and blood parameters of broilers

Abstract: This study aimed to investigate the effect of lactic acid bacteria (LAB) and smectite on the growth performance, nutrient digestibility and blood parameters of broilers that were fed diets contaminated with aflatoxin B (AFB ). A total of 480 newly hatched male Arbor Acres broilers were randomly allocated into four groups with six replicates of 20 chicks each. The broilers were fed diets with the AFB (40 μg/kg) challenge or without (control) it and supplemented with smectite (3.0 g/kg) or LAB (4.0 × 10 CFU/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
(48 reference statements)
6
25
2
Order By: Relevance
“…Almost similar to our results, the addition of 1 mg AFB 1 /kg to Hubbard male broiler chickens from 1 to 42 d ( Modirsanei et al., 2008 ), 2 mg/kg of diet to broiler chickens ( Shannon et al., 2017 ), 1 mg/kg of diet to Ross male chickens from 1 to 21 d ( Gowda et al., 2008 ), 40 μg/kg AFB 1 to Arbor Acres broiler chickens ( Liu et al., 2018 ), and 2.5 mg AFB 1 /kg to Japanese quails ( Bagherzadeh Kasmani et al., 2012 ) decreased BW, feed intake, FCR, and productive efficiency index. Aflatoxin B1 side effects on growth performance have been related with a decrease in the protein and energy utilization ( Verma et al., 2004 ), probably as a consequence of a deterioration of the digestive and metabolic efficiency of the broiler chickens.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Almost similar to our results, the addition of 1 mg AFB 1 /kg to Hubbard male broiler chickens from 1 to 42 d ( Modirsanei et al., 2008 ), 2 mg/kg of diet to broiler chickens ( Shannon et al., 2017 ), 1 mg/kg of diet to Ross male chickens from 1 to 21 d ( Gowda et al., 2008 ), 40 μg/kg AFB 1 to Arbor Acres broiler chickens ( Liu et al., 2018 ), and 2.5 mg AFB 1 /kg to Japanese quails ( Bagherzadeh Kasmani et al., 2012 ) decreased BW, feed intake, FCR, and productive efficiency index. Aflatoxin B1 side effects on growth performance have been related with a decrease in the protein and energy utilization ( Verma et al., 2004 ), probably as a consequence of a deterioration of the digestive and metabolic efficiency of the broiler chickens.…”
Section: Discussionsupporting
confidence: 88%
“…The basic mechanism seems to involve chemisorption of AFs in the GIT and reduction their bioavailability ( Chen et al., 2014 ). In addition, addition of diatomaceous ( Modirsanei et al., 2008 ), LAB, and smectite ( Liu et al., 2018 ) and 74 and 222 mg total curcumnoids/kg of diet ( Zhang et al., 2016 ) improved broiler chickens performance as it was comparable with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the per gram yolk concentrations of triglyceride, cholesterol, phospholipid, and phosvitin were also influenced by the dietary LAB in the present study. This was similar to the report that LAB increased hemoglobin, albumin and total protein, but decreased cholesterol, total bilirubin, creatinine of broilers (Liu et al, 2018c;Wang et al, 2018). Others reported that L. acidophilus (strain D2/CSL CECT 4529) decreased egg lipid content of laying hens (Forte et al, 2016); L. plantarum (strain MDL1118) and E. faecium strain (MDF1104) removed yolk cholesterol by 58 and 38%, respectively, when incubated in medium containing 4% egg yolk (Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Montmorillonite ( MMT ), an aluminosilicate mineral clay, has particular physical and chemical properties, such as large surface area, strong adsorptive capacity, and standout adhesive capability ( Segad et al., 2010 ). The MMT can alleviate the adverse effects of mycotoxin-contaminated diets and reduce the population of pathogenic bacteria in the intestinal tract of poultry ( Liu et al., 2018 , Qu et al., 2018 , Chen et al., 2019a ). Our recent study has demonstrated that MMT can enhance gut barrier functions of laying hens in late production ( Chen et al., 2019c ).…”
Section: Introductionmentioning
confidence: 99%